ChemInform Abstract: Synthesis and Tautomerization of Hydroxylated Isoflavones Bearing Heterocyclic Hemi‐Aminals. Issue 21 (May 2015) - Frasinyuk, Mykhaylo S.; Bondarenko, Svitlana P.; Khilya, Volodymyr P.; Liu, Chunming; Watt, David S.; Sviripa, Vitaliy M.
Abstract Isoflavones (I) undergo Mannich reaction with amino alcohols such as (III), (V), as well as (VII) and an excess formaldehyde (II) to afford in principle two tautomeric products that incorporate two molecules of HCHO for each equivalent amino alcohol.